Cullen's sign and massive ovarian enlargement secondary to primary hypothyroidism in a patient with a normal FSH receptor. Issue 6 (19th May 2006) - Sultan, A; Velaga, M R; Fleet, M; Cheetham, T
Abstract : Ovarian hyperstimulation is a recognised complication of longstanding hypothyroidism. A 12 year old girl with atrophic thyroiditis who presented with abdominal pain and distension is reported. She was noted to have bruising in the vicinity of the umbilicus (Cullen's sign). She had pronounced ovarian enlargement on ultrasonography and it was hypothesised that this profound phenotype might reflect an abnormal FSH receptor. However sequencing of the FSH receptor was normal. The ovarian enlargement resolved with thyroxine replacement. Physicians and surgeons should consider longstanding hypothyroidism in patients presenting with Cullen's sign.